Planning strategy for Tukad Bindu destination as a tourist Attraction in Denpasar city - I Wayan Agus Ananda Putra; Francisca Titing Koerniawaty; I Made Darsana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Tukad Bindu is one on the river-based tourist attractions in Denpasar Bali which has been visited by domestic tourists. However, it has not got a well planning strategy to establish this tourism sites sustainably and become a competitive destination in Denpasar City. This research aims to identify the development potential along Tukad Bindu, Denpasar, Bali, using qualitative methods and applying SWOT analysis. The research location focused on the revitalization of the river as a driver of tourism and increased agricultural productivity, tourist attractions, and active community participation. The results showed that the S-O (Strengths-Opportunity) strategy can be applied by preserving river revitalization as a carrying capacity for tourism while increasing agricultural productivity and tourist attractions. The S-T (Strengths-Threats) strategy can be done by empowering the community through active participation to overcome potential threats. The W-O (weaknesses-opportunities) strategy involves providing education and counselling through the Denpasar City Environment Agency to local communities. Meanwhile, the W-T (Weaknesses-Threats) strategy emphasizes cooperation with the government and the private sector to increase tourism promotion, develop cultural agricultural attractions, and maintain the sustainability of the program in the future. This research recommends the implementation of these strategies as concrete steps in maximizing the development potential around Tukad Bindu, Denpasar, and Bali. The implementation of these strategies is expected to have a positive impact on tourism, agriculture, and the welfare of the local community.